ENTREPRENEURIAL LEADERSHIP: A THEORETICAL FRAMEWORK - Esmer, Yusuf; Dayi, Faruk (Mehmet Akif Ersoy Universitesi Iktisadi ve Idari Bilimler Fakultesi Dergisi, 2017)
Today, having just leadership or entrepreneurship qualities by business managers is not enough for success of enterprises. Managers need to have both leadership and entrepreneurship qualities in order to be successful. At this point, the concept of entrepreneurial leadership emerges. Entrepreneurial leadership is a new and modern type of leadership that is a combination of leadership qualities and spirit of entrepreneurship. In addition, entrepreneurial leadership is creating new products, new processes and expansion opportunities in existing businesses, working in social institutions and dealing with ignored social issues, participating in social and political movements, contributing to the change of current services and policies implemented by civil society organizations and governments. In recent times, entrepreneurial leadership has become a new phenomenon in business management that needs to be discussed. In this regard, in this study, the importance of entrepreneurial leadership is emphasized by examining the concept of entrepreneurial leadership within a theoretical framework.
Keywords: leadership; enterprise; Social Sciences; girişimcilik; entrepreneurship; H; Entrepreneurship; Leadership; Entrepreneurial leadership; Management; Enterprise; Girişimcilik; Liderlik; Girişimci Liderlik; Yönetim; İşletme; i̇şletme; Business Administration; H1-99; entrepreneurial leadership; liderlik; Entrepreneurship; girişimci liderlik; Management; Social sciences (General); Leadership; yönetim; İşletme; Entrepreneurial leadership; Enterprise; management; 16. Peace & justice; 8. Economic growth